Influence of fabrication processing on phase transition and electrical properties of 0.8Pb(Zr1/2Ti1/2)O3-0.2Pb(Ni 1/3Nb2/3)O3 ceramics - Rujijanagul G. (2014)
The binary system of 0.8Pb(Zr1/2Ti1/2)O3-0.2Pb(Ni 1/3Nb2/3)O3 ceramics were synthesized by conventional mixed oxide and columbite method. X-ray diffraction analysis demonstrated the coexistence of both the rhombohedral and tetragonal phases for the columbite prepared sample. Rhombohedral to tetragonal phase transition for columbite method was different compared with those of the mixed oxide method. The permittivity shows a shoulder at the rhombohedral to tetragonal phase transition temperature TRho-Tetra = 195 °C, and then a maximum permittivity (36,000 at 10 kHz) at the transition temperature Tm = 277 °C on ceramics prepared with the columbite method. However, piezoelectric coefficient (d33) was measured to be 282 pC/N for the conventional method and higher than the columbite method. The results were related to the phase compositions and porosity of the ceramics. © 2007 Elsevier B.V. All rights reserved.